On modified Picard and Gauss—Weierstrass singular integrals - Rempulska, L.; Walczak, Z. (Український математичний журнал, 2005)
We introduce a certain modification of the Picard and Gauss—Weierstrass singular integrals and prove approximation theorems for them. Введено деяку модифікацію сингулярних інтегралів Пікара та Гаусса - Вейєрштрасса, a також доведено апроксимаційні теореми для цих інтегралів.